Examining the long-term effects of traumatic brain injury on fear extinction in male rats - Smith, K. A.; Raskin, M. R.; Donovan, M. H.; Raghunath, V.; Mansoorshahi, S.; Telch, M. J.; Shumake, J.; Noble-Haeusslein, L. J.; Monfils, M. H. (Frontiers in Behavioral Neuroscience, 2023)
There is a strong association between traumatic brain injuries (TBIs) and the development of psychiatric disorders, including post-traumatic stress disorder (PTSD). Exposure-based therapy is a first-line intervention for individuals who suffer from PTSD and other anxiety-related disorders; however, up to 50% of individuals with PTSD do not respond well to this approach. Fear extinction, a core mechanism underlying exposure-based therapy, is a procedure in which a repeated presentation of a conditioned stimulus in the absence of an unconditioned stimulus leads to a decrease in fear expression, and is a useful tool to better understand exposure-based therapy. Identifying predictors of extinction would be useful in developing alternative treatments for the non-responders. We recently found that CO2 reactivity predicts extinction phenotypes in rats, likely through the activation of orexin receptors in the lateral hypothalamus. While studies have reported mixed results in extinction of fear after TBI, none have examined the long-term durability of this phenotype in the more chronically injured brain. Here we tested the hypothesis that TBI results in a long-term deficit in fear extinction, and that CO2 reactivity would be predictive of this extinction phenotype. Isoflurane-anesthetized adult male rats received TBI (n=59) (produced by a controlled cortical impactor) or sham surgery (n=29). One month post injury or sham surgery, rats underwent a CO2 or air challenge, followed by fear conditioning, extinction, and fear expression testing. TBI rats exposed to CO2 (TBI-CO2) showed no difference during extinction or fear expression relative to shams exposed to CO2 (sham-CO2). However, TBI-CO2 rats, showed significantly better fear expression than TBI rats exposed to air (TBI-air). In contrast to previous findings, we observed no relationship between CO2 reactivity and post-extinction fear expression in either the sham or TBI rats. However, compared to the previously observed naïve sample, we observed more variability in post-extinction fear expression but a very similar distribution of CO2 reactivity in the current sample. Isoflurane anesthesia may lead to interoceptive threat habituation, possibly via action on orexin receptors in the lateral hypothalamus, and may interact with CO2 exposure, resulting in enhanced extinction. Future work will directly test this possibility.